Neighbourhood attachment in ethnically diverse areas: Diversity vs. inequality, selection bias and preferences for diversity - Agata Górny; Sabina Toruńczyk-Ruiz (University of Warsaw, Centre of Migration Research (CMR), 2014)
This paper is a reply to the Comment by Oded Stark (2014, forthcoming) on our paper published recently in Urban Studies (Górny & Torunczyk-Ruiz 2014). In that paper, we demonstrated that the negative relationship between ethnic diversity and neighbourhood attachment was moderated by interethnic ties differently for migrants and natives living in ethnically diverse neighbourhoods. In his comment, Stark proposes to interpret our findings within the framework of relative deprivation theory, and to explain the different results for migrants and natives by different preferences for diversity and resulting self-selection processes among the two groups. We argue that relative deprivation and ethnic diversity in a neighbourhood pertain to different dimensions and aspects of social diversity and thus interpreting their effects on neighbourhood attachment within one theoretical framework is problematic. We also claim that preferences for diversity are not a substantial basis for selection bias among migrants and natives, given the role of structural and social-psychological factors in residential choices. We conclude that employing the concept of relative deprivation into the analyses of ethnic diversity effects, neighbourhood attachment, and the self-selection process should acknowledge the role that interethnic ties play in the way natives and migrants define their reference groups.
Keywords: 330; ethnic diversity; economic inequality; neighbourhood attachment; self-selection; preferences for diversity; migration; interethnic relations